2019
DOI: 10.1016/j.isci.2019.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Galectin-9 Controls Dendritic Cell Function by Maintaining Plasma Membrane Rigidity

Abstract: SummaryEndogenous extracellular Galectins constitute a novel mechanism of membrane protein organization at the cell surface. Although Galectins are also highly expressed intracellularly, their cytosolic functions are poorly understood. Here, we investigated the role of Galectin-9 in dendritic cell (DC) surface organization and function. By combining functional, super-resolution and atomic force microscopy experiments to analyze membrane stiffness, we identified intracellular Galectin-9 to be indispensable for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…Therefore, our data suggest that the massive level of plasma Gal-9 in COVID-19 patients serves as a DAMP (34) that exerts its actions on several immune cells such as monocytes/macrophages, NK cells, and neutrophils to exacerbate cytokine storm. In agreement, we found induction of IL-6 and TNF-a by rhGal-9 in PBMCs, in particular, monocytes and NK cells, which is consistent with other reports (61,62). The concentration of Gal-9 needed to evoke these responses was far lower (2,000 pg/ml) than the highest concentration of Gal-9 observed in some patients (.100,000 pg/ml).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, our data suggest that the massive level of plasma Gal-9 in COVID-19 patients serves as a DAMP (34) that exerts its actions on several immune cells such as monocytes/macrophages, NK cells, and neutrophils to exacerbate cytokine storm. In agreement, we found induction of IL-6 and TNF-a by rhGal-9 in PBMCs, in particular, monocytes and NK cells, which is consistent with other reports (61,62). The concentration of Gal-9 needed to evoke these responses was far lower (2,000 pg/ml) than the highest concentration of Gal-9 observed in some patients (.100,000 pg/ml).…”
Section: Discussionsupporting
confidence: 93%
“…Cano et al identified the function of Gal-9 in actin cytoskeleton reorganization. They also described an interaction between Gal-9 and C-type lectin receptor within both the human and murine DC cytosol [ 35 ], which indicates that Gal-9 is an evolutionarily conserved lectin which functions in maintaining the cortical cytoskeleton structure and function of DCs. Furthermore, their study confirmed that intracellular Gal-9 is required for actin polymerization and controls plasma membrane rigidity by enhancing the activity of the actin-binding protein, RAS-related C3 botulinum toxin substrate 1 (Rac-1).…”
Section: Galectin-9 Molecular and Cellular Biologymentioning
confidence: 99%
“…This may result, in part, from impaired DC activation, which is essential for disease onset in pristane-induced autoimmunity ( Richard and Gilkeson, 2018 ). In this case, intracellular Gal9 interacts with the cortical actin cytoskeleton to facilitate phagocytosis and DC activation ( Querol Cano et al, 2019 ), and therefore, genetic deletion of Gal9 may be detrimental for DC-dependent models of autoimmunity. The growing compendium of data suggest that Gal9 may have pleotropic effects that result in context-dependent and cell-type-specific regulation ( Panda and Das, 2018 ).…”
Section: Discussionmentioning
confidence: 99%